The 7Ps Marketing Mix in Hospital Services: A Systematic Mapping of Applications Through a Scoping Review - Rindu, Rindu; Hafizurrachman, Muhammad; Haryanto, Astrid Novita; Zakaria, Wan Nur Amalina (Universitas Pendidikan Indonesia, 2025)
Background: The marketing mix is a vital framework for optimizing hospital services, improving patient satisfaction, and maintaining competitiveness in the healthcare sector. Despite its growing adoption, implementation remains inconsistent, with limited comprehensive reviews evaluating its overall effectiveness.Objective: This scoping review explores the application of the marketing mix in hospital services, identifies key challenges and opportunities, and highlights research gaps to inform future healthcare marketing strategies.Methods: A scoping review was conducted following Arksey and O’Malley’s framework and PRISMA-ScR guidelines. A systematic search across PubMed, Scopus, and Web of Science identified peer-reviewed studies published between 2019 and 2023. Studies focusing on the marketing mix in hospital services were included, while non-peer-reviewed and irrelevant articles were excluded. Data extraction analyzed the implementation of the 7Ps framework and its outcomes.Results: Seven studies examined the marketing mix in hospitals, highlighting key findings. Hospitals differentiate through specialized services, pricing strategies influence affordability, and accessibility affects patient choices. Digital marketing enhances engagement, and expert professionals improve service quality, though workforce shortages pose challenges. Streamlined procedures and modern infrastructure enhance patient experience, but barriers like high service costs, geographic constraints, digital literacy gaps, and operational inefficiencies limit full implementation.Conclusion: The marketing mix is essential for hospital services and patient satisfaction but faces challenges in accessibility, workforce management, and digital transformation. Future research should assess its long-term impact and develop tailored frameworks to enhance hospital marketing effectiveness